Laser assisted synthesis of anisotropic metal nanocrystals and strong light-matter coupling in decahedral bimetallic nanocrystals. Issue 6 (10th February 2021) - Balci, Fadime Mert; Sarisozen, Sema; Polat, Nahit; Guvenc, C. Meric; Karadeniz, Ugur; Tertemiz, Ayhan; Balci, Sinan
Abstract : The advances in colloid chemistry and nanofabrication allowed us to synthesize noble monometallic and bimetallic nanocrystals with tunable optical properties in the visible and near infrared region of the electromagnetic spectrum. Abstract : The advances in colloid chemistry and nanofabrication allowed us to synthesize noble monometallic and bimetallic nanocrystals with tunable optical properties in the visible and near infrared region of the electromagnetic spectrum. In the strong coupling regime, surface plasmon polaritons (SPPs) of metal nanoparticles interact with excitons of quantum dots or organic dyes and plasmon–exciton hybrid states called plexcitons are formed. Until now, various shaped metal nanoparticles such as nanorods, core–shell nanoparticles, hollow nanoparticles, nanoprisms, nanodisks, nanorings, and nanobipyramids have been synthesized to generate plasmon–exciton mixed states. However, in order to boost plasmon–exciton interaction at nanoscale dimensions and expand the application of plexcitonic nanocrystals in a variety of fields such as solar cells, light emitting diodes, and nanolasers, new plexcitonic nanocrystals with outstanding optical and chemical properties remain a key goal and challenge. Here we report laser-assisted synthesis of decahedral shaped noble metal nanocrystals, tuning optical properties of the decahedral shaped nanocrystals by galvanic replacement reactions, colloidal synthesis of bimetallic decahedral shaped plexcitonic nanocrystals, and strong plasmon–plasmon interaction in bimetallic decahedral shaped noble metal nanocrystals near a metal film. We photochemically synthesize decahedral Ag nanoparticles from spherical silver nanoparticles by using a 488 nm laser. The laser assisted synthesis of silver nanoparticles yields decahedral (bicolored) and prism (monocolored) shaped silver nanocrystals. The decahedral shaped nanoparticles were selectively separated from prism shaped nanoparticles by centrifugation. The optical properties of decahedral nanocrystals were tuned by the galvanic replacement reaction between gold ions and silver atoms. Excitons of J-aggregate dyes and SPPs of decahedral bimetallic nanoparticles strongly couple and hence decahedral shaped plexcitonic nanoparticles are prepared. In addition, localized SPPs of decahedral shaped bimetallic nanocrystals interact strongly with the propagating SPPs of a flat silver film and hence new hybrid plasmonic modes (plasmonic nanocavities) are generated. The experimental results are further fully corroborated by theoretical calculations including decahedral shaped plexcitonic nanoparticles and decahedral nanoparticles coupled to flat metal films.